2017
DOI: 10.21746/aps.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Harmful Effects of Parthenium hysterophorus and Management Through Different Approaches”- A review

Abstract: Parthenium hysterophorus is commonly known as congress grass or carrot weed in India. It belongs to Asteraceae family and native to subtropics of North and South America. It is an invasive plant species that disturbs cultivated areas, roadside vegetation, gardens etc. P. hysterophorus is considered as one of the worst weeds responsible for causing health problems in animals and humans viz., dermatitis, asthma and bronchitis besides loss to agriculture and ecosystem. Nowadays, it has become one of the major wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…or compensate for missing records due to human surveys. In contrast, prediction bias exists for areas that have been successfully invaded, as P. hysterophorus is highly susceptible to becoming dominant native species (Ramesh et al., 2017 ). However, the EM predictions obtained from the training of the currently recorded data can better simulate the areas that have been successfully invaded.…”
Section: Methodsmentioning
confidence: 99%
“…or compensate for missing records due to human surveys. In contrast, prediction bias exists for areas that have been successfully invaded, as P. hysterophorus is highly susceptible to becoming dominant native species (Ramesh et al., 2017 ). However, the EM predictions obtained from the training of the currently recorded data can better simulate the areas that have been successfully invaded.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, exposure to carrot weed has shown positive reactions to mAb-2 as well as cytokines [58]. In general, these effects are classified into four categories: airborne contact dermatitis (ABCD), chronic actinic dermatitis (CAD) and the combination of ABCD and CAD and lastly exposure to the sun (photosensitive lichenoid) [57]. Therefore there is a need of more research to know exactly the compounds present in the pollen of this weed which is responsible for the health problems to a human being to make easy management with precaution during physical control practice.…”
Section: Impact Of Carrot-weed On Humanmentioning
confidence: 99%
“…Human contact with carrot-weed followed with exposure to sun results to health effects such as violaceous papulae, as well as a plaque on exposed parts such ears, forehead, cheek and upper chest. Nevertheless, health effects like hyperkeratotic papule and prurigo nodules have been associated with exposure to carrot-weed[57]. On other hands,[58] further showed that dermatitis health effects are due to the presence of a cytotoxic compound sesquiterpene lactone Parthenin.…”
mentioning
confidence: 99%